R248W mutations in p53 gene are rare among Indian patients with head-and-neck cancer - Ashna Gauthaman; Anbalagan Moorthy (Indian Journal of Medical and Paediatric Oncology)
Aim: Cancer is one of the curses to humankind, decades of research in eradicating the disease from the society is proven difficult. Close interaction between clinicians and scientists helps us to translate clinical observations into molecular mechanism of the disease. The Cancer Genome Atlas data suggest that genetic alterations in p53 gene play a crucial role in head-and-neck squamous cell carcinoma (HNSCC) tumorigenesis. Understanding p53 aberrations and their impact on other cellular activities can help with the design of new, more effective therapeutic strategy that target p53 mutation-bearing HNSCC, thereby producing a personalized medicine approach for the disease. Materials and Methods: In an effort to identify the role of R248W mutation of p53 gene in HNSCC patients of Indian origin, tumor samples were collected from 55 patients (n = 55), and polymerase chain reaction–restriction fragment length polymorphism technique was used to screen for the mutation using genomic DNA isolated from the tumors. Results: The results reveal that except for one patient (heterozygous), all the patients were negative for the mutation. Conclusion: These results suggest that p53 R248W mutations are less prevalent in HNSCC Indian patients.